Probing Micro-Newton Forces on Solid/Liquid/Gas Interfaces Using Transmission Phase Shift - Huang, Xianfu (Langmuir : the ACS journal of surfaces and colloids, 2019)
Many of the nature and life systems are driven by capillary interactions on solid/liquid/gas interfaces. Here, we present a profilometry technique called transmission phase shift for visualizing the liquid/gas interfaces in three dimensions with high resolution. Using this approach, we probe the change in tiny forces with particle radius at a solid/liquid/gas interface. We provide the first direct evidence that in the issues of floating versus sinking at small-scale, Archimedes' principle should be generalized to include the crucial role of surface tension and reveal the dominant regimes of floating particles based on the Bond number. Remarkably, the measured forces are in the range of micro-Newtons, suggesting that this terse methodology may guide the future design of a liquid microbalance and will be a universal tool for investigating capillarity and interface issues